PERSEPSI WISATAWAN TERHADAP TAMAN WISATA ALAM CAMPLONG, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Dian Kana Huru; Mamie E. Pelondo'u; Nixon Rammang (Wana Lestari, 2021)
This study aims to determine the tourists' perceptions of the natural tourism park area, and to find out the tourists' perceptions of environmental cleanliness in the Camplong natural tourism park. This research was conducted in November 2019 at the Camplong Nature Tourism Park, Kupang Regency, East Nusa Tenggara Province. Tools and materials used in other research: Cameras, stationery, and questionnaires. The methods used in this study were observation, interview and documentation methods. The results showed that visitors' perceptions of all attractions Camplong natural tourist park is in the "interesting" category with a percentage of 77%; and visitor satisfaction in carrying out all activities (enjoying the attraction) is in the category of "satisfactory with a percentage of 75%; visitor perceptions of all services consisting of: accessibility is in the category of "quite supportive with a percentage of 67%; the physical condition of the facility is in the "good" category with a percentage of 74%; the cleanliness of the facility is in the "clean" category with a percentage of 71%, and the satisfaction of using the facility is in the "satisfactory" category with a percentage of 67%. There is a very large impact on interest in visiting, this can be seen from the high perception and several statements which indicate that the main impetus for tourists to visit is based on the attractiveness factor and service at the Camplong natural tourist park.